OVERVIEW OF KNOWLEDGE ABOUT ASI EXCLUSIVE PREGNANT WOMEN IN BPM INDRAWATI MARZUQOH POLANHARJO VILLAGE DISTRICT WANGEN KLATEN - Setiyati .; Sumantri .; Ekawati . (STIKES DUTAGAMA KLATEN, 2013)
Background: Mother's Milk is the first food, main, and best for the baby that is natural because milk contains a variety of nutrients needed in the process of growth and development of infants. Interruption of breastfeeding in principle rooted in lack of knowledge, confidence, and lack of support from family and the environment. Objective: To reveal the knowledge of pregnant women about exclusive breastfeeding in the village of Wangen BPM Indrawati, Polanharjo subdistrict, Klaten regency. Methods: This research is a quantitative study using a descriptive research design. Sampling with purposive sampling technique. The population is pregnant women who come for ANC (Ante Natal Care) in BPM Indrawati, except primi gravida mothers first trimester. As for the number of visits of pregnant women in BPM Indrawati in this study were 36 pregnant women. Results: Maternal Knowledge on exclusive breastfeeding in rural Marzuqoh BPM Indrawati Polanharjo Wangen district of Klaten districts included in both criteria, namely 85.09%. Characteristics of pregnant women that include education, employment, maternal education are as follows mostly high school education by 20 respondents (55.56%), and secondary education by 9 respondents (25%) of respondents work As for pregnant women, the majority of pregnant women do not work as many as 22 respondents (61.11%). Maternal characteristics known to primigravida by 10 respondents (27, 78%), mother-multigravid scundi by 26 respondents (72.22%). Knowledge of pregnant women about breastfeeding exclusive breastfeeding on the definition of the criteria included in the 72.22 that is enough, in terms of the composition of breast milk is included in both criteria are 85.76%, while in terms of the benefits of breastfeeding are included in both criteria, namely 91.67%. Conclusions: Maternal Knowledge Preview of exclusive breastfeeding in rural Marzuqoh BPM Indrawati Polanharjo Wangen district of Klaten districts included in both criteria, namely 85.09%.